Primer encuentro de los egresados del Postgrado de Pediatría Autores/as - Prado López, Lidia María (Acta Pediátrica Hondureña, 2015)
Acta Pediátrica Hondureña, Vol. 4, No. 2 / Octubre 2013 a Marzo 2014